Defects characterisation and studies of structural properties of sol–gel synthesised MgFe2O4 nanocrystals through positron annihilation and supportive spectroscopic methods. Issue 1 (2nd January 2020) - Abraham, Ann Rose; Raneesh, B.; Nambissan, P. M. G.; Sanyal, D.; Thomas, Sabu; Kalarikkal, Nandakumar
ABSTRACT: Magnesium ferrite (MgFe2 O4 ) nanocrystalline samples were prepared by sol–gel method and by sintering at temperatures from 300°C to 1000°C. X-ray diffraction and electron microscopic studies showed an increase in crystallite sizes and a decrease in lattice constants at higher sintering temperatures. UV-Vis absorption measurements depicted blue shift for samples of smaller crystallite sizes ( d c ) with a resultant increase of the band gap energies ( Eg . = 2.07 eV at d c  = 49 nm to 3.10 eV at d c  = 6 nm, for samples sintered at 1000°C and 300°C, respectively). Fourier transform infrared spectroscopy of the samples proved the formation of the spinel structure while energy dispersive X-ray analysis pointed out the non-stoichiometric composition, which implied the presence of vacancy type defects that could modify the structural and magnetic characteristics of the compounds. This necessitated the use of positron annihilation lifetime and coincidence Doppler broadening spectroscopic studies for defect characterisation and the results indicated distinct redistribution of cations within the unit cells, making the compound overwhelmingly turn towards a normal spinel configuration at smaller nanocrystalline sizes. Positrons were trapped in larger vacancies of increasing numbers in smaller crystallites. The vacancies turned out to be formed at the octahedral sites where the increased ionic radius of Fe 3+ became large enough to reduce the occupancy significantly. Mossbauer spectra analysis indicated an increase of the ferromagnetic properties in samples sintered at higher temperatures. At 300°C and 400°C, the samples dominantly showed paramagnetic behaviour.